AICCRA Country Scaling Vision: Kenya - Crane, Todd A. (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
The conceptual framework below is a schematic representation of how our various engagement strategies impact the integrated CSA/CIS technology and information ecosystem. Black boxes represent partners and beneficiaries. The red texts represent our contributions. On the left side of the diagram, we are supporting the national public sector with information tools that strengthen capacity of meteorological services and bundled ag/climate advisories. Along with complementary trainings, these are disseminated (green lines) directly to producers and local public and private sector partners who are being trained in using them to advise producers. AICCRA Kenya is also mainstreaming gender inclusivity throughout its programming. The gender equality symbol indicates the products for which we have developed specific gender inclusion strategies, both in terms of technological dissemination and training materials. Supporting both direct and indirect impact pathways for producers, we are building redundancy in the system, which should improve social inclusion, institutional robustness and sustainability of application of these advisories.